Oral immunotherapy for Immunoglobulin E‐mediated cow's milk allergy in children: A systematic review and meta analysis. Issue 10 (15th September 2022) - Tang, Lujing; Yu, Yu; Pu, Xiangyuan; Chen, Jie
Abstract: Backgound: Cow's milk allergy (CMA) is the most common allergy in infants that decreases the quality of life of patients and their families. Standard treatment for CMA is the strict avoidance of milk; new treatment strategies such as oral immunotherapy (OIT) have been sought for patients with CMA. We aimed to assess the clinical efficacy and safety of OIT in the treatment of children with immunoglobulin E‐mediated CMA (IMCMA). Methods: We searched all randomized controlled trials in which OIT is used to treat children with IMCMA from five international electronic databases. We estimated a pooled risk ratio (RR) for each outcome using a Mantel–Haenzel fixed‐effects model if statistical heterogeneity was low. Results: Eleven studies were chosen for meta‐analysis, including a total of 469 children (242 OITs, 227 controls). One hundred and seventy‐six patients (72.7%) in the OIT were desensitized compared with 49 patients (21.6%) in the control group (RR: 7.35, 95% confidence interval (CI): 2.82–19.13, p < .0001). The desensitization effect of OIT was particularly significant in children over 3 years old (RR: 18.05, 95% CI: 6.48–50.26, p < .00001). Although adverse effects were common, they usually involved mild reactions, but epinephrine use was more common in the OIT group (RR: 7.69, 95% CI: 2.16–27.33, p < .002). Conclusion: OIT can lead to desensitization in the majority of individuals with IMCMA, especially in patients over 3 years old. A major problem of OIT is the frequency of adverse events, although most are mild. OIT may be an alternative treatment in the future. Abstract : We conduct a latest meta‐analysis; the analyses show that oral immunotherapy (OIT) is effective for immunoglobulin E‐mediated cow's milk allergy in children, especially in patients older than 3 years. OIT can cause adverse actions but most are mild‐to‐moderate.